2017
DOI: 10.18632/oncotarget.19640
|View full text |Cite
|
Sign up to set email alerts
|

Progress and future prospect of in vitro spermatogenesis

Abstract: Infertility has become a major health issue in the world. It affects the social life of couples and of all infertility cases; approximately 40–50% is due to “male factor” infertility. Male infertility could be due to genetic factors, environment or due to gonadotoxic treatment. Developments in reproductive biotechnology have made it possible to rescue fertility and uphold biological fatherhood. In vitro production of haploid male germ cell is a powerful tool, not only for the treatment of infertility including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 152 publications
0
38
0
2
Order By: Relevance
“…The majority of male infertility problems are caused by spermatogenic defects. Spermatogenesis is a highly complex process in which a large number of genes and proteins function together, and very few genes have been identified that are known to cause SCOS in this process . Del of a genomic segment can result in hemizygosity for the deleted segment and cause loss of function or mutation in the normal allele, thus leading to failure in prevention of the disease by this allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of male infertility problems are caused by spermatogenic defects. Spermatogenesis is a highly complex process in which a large number of genes and proteins function together, and very few genes have been identified that are known to cause SCOS in this process . Del of a genomic segment can result in hemizygosity for the deleted segment and cause loss of function or mutation in the normal allele, thus leading to failure in prevention of the disease by this allele.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis is a highly complex process in which a large number of genes and proteins function together, and very few genes have been identified that are known to cause SCOS in this process. 16 Del of a genomic segment can result in hemizygosity for the deleted segment and cause loss of function or mutation in the normal allele, thus leading to failure in prevention of the disease by this allele. An increased number of copies, such as Amp, can cause imbalances due to the overexpression of duplicated genes, or, when intragenic can alter product structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…The A dark spermatogonia were referred to as the reserve stem cells that rarely divide, but can be launched to self‐renew in the event of injury or disease, whereas the A pale spermatogonia were considered the self‐renewing stem cells (Dym, Kokkinaki, & He, ; Waheeb & Hofmann, ). Type B spermatogonia represent the differentiated cells that divide into preleptotene spermatocytes that undergo meiosis (Ibtisham et al, ).…”
Section: Overview Of Sscs Self‐renewalmentioning
confidence: 99%
“…the differentiated cells that divide into preleptotene spermatocytes that undergo meiosis (Ibtisham et al, 2017).…”
mentioning
confidence: 99%
“…Mammalian spermatogenesis is a network of developmental process to which a specialised form of spermatozoa is formed by the transformation of diploid progenitor germ cell (Ibtisham et al, 2017). Mammalian spermatogenesis is a network of developmental process to which a specialised form of spermatozoa is formed by the transformation of diploid progenitor germ cell (Ibtisham et al, 2017).…”
Section: Introductionmentioning
confidence: 99%